A fibrous carbon-based electromagnetic wave absorbing material and a method for preparing the same
Patent Information
- Application Number
- CN202611117680.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-27
AI Technical Summary
由于纳米粒子比表面能大,极易团聚,导致磁性组分无法在碳基体中实现分子级均匀分布
本发明提供的这种纤维碳基电磁波吸收材料,通过将连续碳基体、磁性金属粒子和纳米增强相进行复合,利用纤维碳网络的导电损耗、磁性组分的磁损耗以及SiC引起的介电损耗和界面极化损耗之间的协同作用,显著提高了材料的电磁波吸收性能。
Smart Images

Figure CN122622222B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave absorbing materials technology, specifically relating to a fiber-based carbon electromagnetic wave absorbing material and its preparation method. Background Technology
[0002] With the rapid development of electronic information technology and electronic devices, the problem of electromagnetic radiation has become increasingly prominent. Electromagnetic waves not only affect the normal operation of precision electronic equipment, but may also pose a potential threat to human health. Therefore, the development of electromagnetic wave absorbing materials with the comprehensive characteristics of "thin, light, wide, and strong" has become a research hotspot in the field of functional materials.
[0003] Currently, electromagnetic wave absorbing materials are mainly classified into magnetic absorbing materials, dielectric loss materials, and multi-component composite absorbing materials. Among them, carbon-based materials (such as carbon fibers, carbon nanotubes, and graphene) are considered ideal lightweight absorbing matrices due to their advantages such as light weight, tunable conductivity, excellent chemical stability, and ease of structural design. However, single carbon-based materials are limited by poor impedance matching and a single loss mechanism (only dielectric loss), making it difficult to achieve broadband strong absorption.
[0004] To overcome the aforementioned bottlenecks, existing technologies typically combine magnetic metals such as Fe, Co, and Ni, or their oxides, with carbon materials to introduce magnetic losses and improve impedance matching. However, this technology still has the following significant shortcomings: First, existing methods mostly employ physical ball milling or solution blending to directly mix micron / nano-sized magnetic powders with carbon precursors. Due to the high specific surface energy of nanoparticles, they are prone to agglomeration, preventing the magnetic components from achieving a uniform molecular-level distribution within the carbon matrix. This not only weakens the synergistic effect between magnetic and dielectric losses but also, due to the mismatch in thermal expansion coefficients between the agglomerates and the carbon matrix, causes stress concentration and interfacial delamination during subsequent carbonization, severely degrading the material's structural integrity and mechanical properties.
[0005] Second, while common post-loading methods (such as impregnation and electroless plating) can deposit magnetic particles onto the surface of carbon materials, the particles only adhere to the outer surface, resulting in weak adhesion, easy detachment, and often clogging of the conductive network of the carbon matrix or damaging the original morphology of the fibers. In addition, multi-step composite processes are lengthy and complex, making it difficult to achieve controllable distribution of magnetic components and ceramic phases at the nanoscale, thus limiting further improvement in microwave absorption performance.
[0006] Third, existing technologies struggle to simultaneously achieve both "good impedance matching" (allowing electromagnetic waves to enter the material) and "strong attenuation capability" (rapidly dissipating incoming electromagnetic waves) at extremely thin thicknesses. Specifically, while highly conductive carbon matrices provide strong dielectric loss, they also result in strong surface reflection, making it difficult for electromagnetic waves to enter; conversely, reducing conductivity sacrifices attenuation capability. Balancing these two contradictions through reasonable microstructure design within a thickness limit (≤2 mm) is a major challenge currently facing technology.
[0007] Therefore, there is an urgent need in this field to develop a novel carbon-based composite microwave absorbing material that can achieve uniform and stable co-dispersion of magnetic components in a carbon matrix without destroying the continuous fiber network structure. Summary of the Invention
[0008] The purpose of this invention is to provide a carbon-based electromagnetic wave absorbing material to solve the aforementioned technical problems existing in the prior art.
[0009] Therefore, the technical solution provided by the present invention is as follows: A fiber-based carbon electromagnetic wave absorbing material includes a continuous carbon matrix, magnetic metal particles, and a nano-reinforcing phase. The continuous carbon matrix is formed by carbonizing a carbon precursor at high temperature. Both the carbon precursor and the magnetic metal particles are dissolved in N,N-dimethylacetamide. The magnetic metal particles are uniformly anchored and embedded in the continuous carbon matrix. The nano-reinforcing phase is uniformly dispersed within the framework of the continuous carbon matrix by physical embedding.
[0010] The fiber-based carbon-based electromagnetic wave absorbing material provided by this invention dissolves carbon precursors and magnetic metal particles in N,N-dimethylacetamide (DMAc). DMAc not only acts as a solvent, but its molecules also undergo coordination reactions with metal ions to form a complex ion Co(DMAc)6. 2+ This helps metal ions to be uniformly dispersed at the molecular level, and nano-silicon carbide (SiC) powder is uniformly dispersed in the spinning solution as a reinforcing phase. When the fiber film is prepared by electrospinning, coordination bonds will be formed between the carbon precursor and the magnetic metal particles, which will "anchor" the magnetic components in the fiber skeleton. At the same time, the dispersed SiC particles, as a rigid heterogeneous phase, build a nano-reinforcing network inside the fiber.
[0011] This invention utilizes an interlaced network of carbon fibers to form a conductive network, enhancing impedance matching; SiC nanoparticles enhance dielectric loss and synergize with magnetic metals, significantly improving the material's electromagnetic wave absorption performance.
[0012] Furthermore, the carbon precursor is polyacrylonitrile or polyvinylpyrrolidone.
[0013] Furthermore, the magnetic metal particles are cobalt acetylacetonate, iron acetylacetonate, or nickel acetylacetonate.
[0014] Furthermore, the nano-reinforcing phase is SiC.
[0015] Nano-SiC powder is used as a reinforcing phase and is uniformly dispersed in the spinning solution by high-energy ultrasound or high-speed shearing.
[0016] Furthermore, the mass ratio of the continuous carbon matrix, magnetic metal particles, and nano-reinforcing phase is 1~1.5:0.5~0.75:0.5~0.75.
[0017] Furthermore, the molecular weight Mw of the carbon precursor is 150,000 to 250,000 g / mol.
[0018] Mw is used to measure the length of a polymer chain, reflecting the size of a single molecule. It represents the average degree of polymerization of the polymer, determining the material's mechanical properties and processing fluidity. Therefore, taking polyacrylonitrile (PAN) as an example, the molecular weight of PAN used for spinning is limited to between 150,000 and 250,000 g / mol. The higher the molecular weight, the longer the molecular chain, and the higher the strength of the spun fiber may be, but the more difficult it is to dissolve.
[0019] Furthermore, the magnetic metal particles have an average particle size of 5-70 μm, and the nano-reinforcing phase has an average particle size of 3-10 μm.
[0020] The average particle size of the magnetic metal particles and nano-reinforcing phase determines their dispersion stability in the spinning solution and the reinforcing effect of the final film. If the particle size is too large, large particles form stress concentration points in the carbon matrix, leading to fiber brittleness and deterioration of mechanical properties; it also causes impedance mismatch, weakens magnetic permeability and interfacial polarization, and clogs the spinning needles, disrupting the molding process. If the particle size is too small, it cannot provide magnetic loss; excessively small particles are prone to agglomeration and ripening during high-temperature carbonization, making SiC difficult to disperse, and excessive interfaces can bind charge carriers, weakening conductivity loss.
[0021] This invention also provides a method for preparing a fiber-based carbon electromagnetic wave absorbing material, comprising the following steps: Step 1) The carbon precursor and magnetic metal salt are dissolved sequentially in N,N-dimethylacetamide to form a homogeneous and stable spinning solution; Step 2) Add the nano-reinforcing phase to the spinning solution and disperse it evenly to prepare a composite suspension spinning solution; Step 3) The composite suspension spinning solution is used to prepare a fiber film by electrospinning; Step 4) Dry the fiber film at room temperature for 10-12 hours to stabilize the fiber structure, then perform high-temperature carbonization treatment in an inert atmosphere, keep it at the temperature for 1-2 hours, and cool it naturally to room temperature to obtain the electromagnetic wave absorbing material.
[0022] In this invention, coordination occurs between the carbon precursor and magnetic metal particles, forming coordination bonds with metal ions (such as Fe³⁺, Co²⁺, etc.), thereby fixing the magnetic metal particles in the carbon precursor matrix. At the same time, the solvent DMAc itself also actively participates. For divalent transition metal ions (such as Co²⁺, Ni²⁺, etc.), DMAc molecules act as ligands, forming a stable solvation layer around the metal ions.
[0023] Furthermore, the parameters for electrospinning in step 3) are as follows: voltage is 25~30kv, thrust speed is 0.004~0.006mm / s, needle is 20G, and the distance between the push pump and the roller is 10~15cm.
[0024] Furthermore, the high-temperature carbonization temperature mentioned in step 4) is 1000~1200℃.
[0025] The beneficial effects of this invention are as follows: The fiber-carbon-based electromagnetic wave absorbing material provided by this invention significantly improves the electromagnetic wave absorption performance of the material by combining a continuous carbon matrix, magnetic metal particles and nano-reinforcing phases, and utilizing the synergistic effect between the conductive loss of the fiber carbon network, the magnetic loss of the magnetic components, and the dielectric loss and interfacial polarization loss caused by SiC. Attached Figure Description
[0026] Figure 1 This is a scanning electron microscope image of the Co / SiC@PAN fiber in an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of Co / SiC@CPAN-1000 in an embodiment of the present invention; Figure 3 This is a scanning electron microscope image of Co / SiC@CPAN-1100 in an embodiment of the present invention; Figure 4 This is a scanning electron microscope image of Co / SiC@CPAN-1200 in an embodiment of the present invention; Figure 5 This is a microwave absorption performance diagram of Co / SiC@CPAN-1000 in an embodiment of the present invention; Figure 6 This is a microwave absorption performance diagram of Co / SiC@CPAN-1100 in an embodiment of the present invention; Figure 7 This is a microwave absorption performance diagram of Co / SiC@CPAN-1200 in an embodiment of the present invention; Figure 8 This is a microwave absorption performance diagram of Fe / SiC@CPAN-1200 in an embodiment of the present invention; Figure 9This is a microwave absorption performance diagram of Ni / SiC@CPAN-1000 in an embodiment of the present invention; Figure 10 This is a waveform absorption performance diagram of Co@CPAN-1000 in the comparative example of this invention; Figure 11 This is a waveform absorption performance diagram of Co@CPAN-1100 in the comparative example of this invention; Figure 12 This is a waveform absorption performance diagram of Co@CPAN-1200 in the comparative example of this invention. Detailed Implementation
[0027] The following specific embodiments illustrate the implementation of the invention. Those skilled in the art can easily understand other advantages and effects of the invention from the content disclosed in this specification.
[0028] Exemplary embodiments of the invention are now described with reference to the accompanying drawings. However, the invention may be embodied in many different forms and is not limited to the embodiments described herein. These embodiments are provided to fully and completely disclose the invention and to fully convey its scope to those skilled in the art. The terminology used in the exemplary embodiments illustrated in the drawings is not intended to limit the invention.
[0029] Unless otherwise stated, the terms used herein (including technical terms) have their common meaning as understood by one of ordinary skill in the art. Furthermore, it is understood that terms defined in commonly used dictionaries should be understood to have a meaning consistent with the context of their relevant field, and not to be interpreted as having an idealized or overly formal meaning.
[0030] This invention provides a fiber-based carbon electromagnetic wave absorbing material, comprising a continuous carbon matrix, magnetic metal particles, and a nano-reinforcing phase. The continuous carbon matrix is formed by carbonizing a carbon precursor at high temperature. Both the carbon precursor and the magnetic metal particles are dissolved in N,N-dimethylacetamide. The magnetic metal particles are uniformly anchored and embedded in the continuous carbon matrix. The nano-reinforcing phase is uniformly dispersed within the framework of the continuous carbon matrix by physical embedding.
[0031] Furthermore, the carbon precursor is polyacrylonitrile, polymethyl methacrylate, or polyvinylpyrrolidone.
[0032] Furthermore, the magnetic metal particles are cobalt acetylacetonate, iron acetylacetonate, or nickel acetylacetonate.
[0033] Furthermore, the nano-reinforcing phase is SiC.
[0034] Example 1 This embodiment provides a fibrous carbon-based electromagnetic wave absorbing material, wherein the continuous carbon matrix is polyacrylonitrile (PAN) (M).w The magnetic metal particles (cobalt acetylacetonate (purchased from Shanghai Asus Biotechnology Co., Ltd.) at a concentration of 150,000 g / mol) were used, and the nano-reinforcing phase was SiC (purchased from Shanghai Maclean Biochemical Co., Ltd.). The preparation process is as follows: Step 1) Preparation of Co / SiC@PAN fibers Co / SiC@PAN fibers were prepared by electrospinning. First, 1g of PAN and 0.5g of cobalt(III) acetylacetonate were dissolved in 10ml of DMAc, and then 0.5g of SiC nanoparticles were added. The mixture was magnetically stirred for 4-6 hours. Then, 10ml of the mixture was taken using a syringe and electrospinned.
[0035] The experimental parameters for electrospinning are as follows: voltage 28kV, thrust speed 0.006mm / s, needle 20G, and distance between the push pump and the roller 12cm.
[0036] Step 2) Preparation of Co / SiC@CPAN carbon fibers The synthesized Co / SiC@PAN fibers were dried at room temperature for 10 h, and then pre-oxidized at 200 °C for 2 h to stabilize the fiber structure. Step 3) Place the carbon in a tube furnace and carbonize it at 1000℃ at a rate of 5℃ / min under an Ar atmosphere (flow rate of 150ml / min). Hold the temperature for 2 hours and allow it to cool naturally to room temperature to obtain Co / SiC@CPAN carbon fiber. This is designated as Co / SiC@CPA-1000.
[0037] Polyacrylonitrile (PAN) is a commonly used carbon precursor, suitable for forming continuous fibers through electrospinning; magnetic metal salts such as cobalt acetylacetonate can form magnetic components during subsequent heat treatment, thereby endowing the material with certain magnetic loss capability; silicon carbide (SiC), as a typical inorganic ceramic material, has good dielectric properties, and its introduction into the carbon-based fiber system is expected to improve the dielectric loss behavior and interfacial polarization effect of the material.
[0038] Principle of this invention: This invention involves sequentially dissolving polyacrylonitrile (PAN) and magnetic metal particles in N-dimethylacetamide (DMAc) to form a homogeneous and stable spinning solution. During this process, DMAc not only acts as a solvent, but its molecules also undergo coordination reactions with metal ions to form complexes such as Co(DMAc)6²⁺, which helps to uniformly disperse the metal ions at the molecular level.
[0039] Subsequently, nano-silicon carbide (SiC) powder is used as a reinforcing phase and is uniformly dispersed in the above spinning solution by high-energy ultrasound or high-speed shearing to prepare a composite suspension spinning solution containing magnetic particles and ceramic fillers.
[0040] The composite suspension was prepared into a fiber film using electrospinning or dry-jet wet spinning processes. During the curing stage, the magnetic metal salt further coordinated and crosslinked with the cyano groups (-C≡N) on the PAN molecular chain, "anchoring" the magnetic component in the fiber skeleton; at the same time, the dispersed SiC particles, as a rigid heterophase, constructed a nano-reinforcing network inside the fiber.
[0041] Finally, the obtained fiber film was subjected to high-temperature carbonization under an inert atmosphere. During this process, PAN underwent cyclization, dehydrogenation, and pyrolysis reactions, transforming into amorphous carbon or disordered graphite structures to form a continuous conductive carbon matrix. Magnetic metal salts decomposed in situ into magnetic metal elements at high temperatures, endowing the film with magnetic responsiveness. Meanwhile, the chemically inert SiC nanoparticles remained stable, uniformly embedded in the carbon matrix as a "rigid framework," effectively suppressing carbonization shrinkage and improving the mechanical stiffness of the film. Ultimately, an ultrathin, self-supporting flexible carbon fiber composite film with conductivity, magnetic responsiveness, and enhanced mechanical properties was obtained.
[0042] The scanning electron microscope image of the Co / SiC@PAN fiber prepared in this embodiment is shown below. Figure 1 As shown in the figure, the uncarbonized Co / SiC@PAN sample is composed of a large number of slender fibers interwoven with each other, forming a relatively uniform and dense two-dimensional / three-dimensional network structure. At the same time, some particulate or sheet-like substances can be observed to be attached to the fiber surface or distributed between the fibers, proving that the uncarbonized Co / SiC@PAN has successfully formed a continuous fiber network structure.
[0043] Scanning electron microscope image of the prepared Co / SiC@CPA-1000 is shown below. Figure 2 As shown, the fibers, even without carbonization, have already curled. After carbonization, the fibers are significantly bent, shrunken, and thinner compared to the uncarbonized sample, transforming from relatively straight fibers into a more curled carbon fiber network. Simultaneously, particles remain attached to the fiber surface or embedded within the network. This demonstrates that carbonization at 1000℃ causes fiber curling and shrinkage, while maintaining network continuity.
[0044] Example 2 The difference between Example 2 and Example 1 is that the carbonization temperature in step 3) is 1100℃, while the other steps are the same. This is denoted as Co / SiC@CPA-1100.
[0045] Example 3 The difference between Example 3 and Example 1 is that the carbonization temperature in step 3) is 1200℃, while the other steps are the same. This is denoted as Co / SiC@CPA-1200.
[0046] Example 4 The difference between Example 4 and Example 3 is that the magnetic metal particles are iron acetylacetonate; all other steps are the same. It is denoted as Fe / SiC@CPA-1200.
[0047] Example 5 Example 5 differs from Example 1 in that the magnetic metal particles are nickel acetylacetonate; all other steps are the same. It is denoted as Ni / SiC@CPA-1200.
[0048] Comparative Example 1 This comparative example provides a fiber-based carbon-based electromagnetic wave absorbing material, the preparation process of which is as follows: Step 1) Preparation of Co / SiC@PAN fibers Co@PAN fibers were prepared by electrospinning. First, 1g of PAN and 0.5g of cobalt(III) acetylacetonate were dissolved in 10ml of DMAc and then magnetically stirred for 4-6 hours. Then, 10ml of the mixture was taken using a syringe and electrospinned.
[0049] The experimental parameters for electrospinning are as follows: voltage 28kV, thrust speed 0.006mm / s, needle 20G, and distance between the push pump and the roller 12cm.
[0050] Step 2) Preparation of Co@CPAN carbon fiber The synthesized Co@PAN fibers were dried at room temperature for 10 h, and then pre-oxidized at 200 °C for 2 h to stabilize the fiber structure; Step 3) Place the carbon in a tube furnace and carbonize it at 1000℃ at a rate of 5℃ / min under an Ar atmosphere (flow rate of 150ml / min). Hold the temperature for 2 hours and allow it to cool naturally to room temperature to obtain Co@CPAN carbon fiber. This is designated Co@CPA-1000.
[0051] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that the carbonization temperature in step 3) is 1100℃, while the other steps are the same. This is denoted as Co@CPA-1100.
[0052] Comparative Example 3 The difference between Comparative Example 3 and Comparative Example 1 is that the carbonization temperature in step 3) is 1200℃, while the other steps are the same. This is denoted as Co@CPA-1200.
[0053] To further illustrate the effects of this invention, performance tests were conducted on the fiber-based electromagnetic wave absorbing materials prepared in Examples 1-5 and Comparative Examples 1-3. The results are shown in Table 1 and... Figures 1-12 .
[0054] Reflection loss curve The measurement method was as follows: A vector network analyzer (VAN; Agilent KEYSIGHT) was used to measure the electromagnetic properties in the 2.0–18.0 GHz range to calculate the absorption characteristics of the EMW. A microwave absorbing coaxial ring was prepared by mixing PAN composite carbon fiber and paraffin wax in a specific ratio.
[0055] Table 1 As shown in Table 1, the frequency range of the electromagnetic wave absorbing material of the present invention with RL < -10 dB covers the C-band to the Ku-band, 4-18 GHz.
[0056] Figure 3 The image shows a scanning electron microscope (SEM) image of Co / SiC@CPAN-1100. It reveals a further increase in fiber crimp, resulting in a more porous, bent, and complex network. Simultaneously, noticeable particle clusters or enrichment are observed on the fiber surface and in localized areas. This demonstrates that carbonization at 1100℃ leads to a richer folded / crepit structure and a more pronounced particle load.
[0057] Figure 4 The image shows a scanning electron microscope (SEM) image of Co / SiC@CPAN-1200. It can be seen that the fibers remain in a coiled and interwoven state, but compared to the 1100℃ sample, some particle clusters are more pronounced, and local aggregation or coarsening may occur. This proves that the fiber network still exists after carbonization at 1200℃, but particle aggregation and structural coarsening are more obvious.
[0058] Figure 5 The graph shows the absorption performance of the Co / SiC@CPAN-1000 electromagnetic wave absorbing material (with a filler ratio of 20%, which refers to a sample-to-paraffin ratio of 2:8 during the preparation of the coaxial ring). The graph shows that when the material thickness is 2.21 mm, the composite material achieves a minimum reflection loss of -51.360 dB at approximately 13.6 GHz and an effective absorption bandwidth of 5.688 GHz, confirming that the Co / SiC@CPAN-1000 composite material possesses strong absorption capabilities and a wide effective absorption bandwidth.
[0059] Figure 6 The graph shows the absorption performance of the Co / SiC@CPAN-1100 electromagnetic wave absorbing material (fill rate 20%). It can be seen from the graph that when the thickness is 3.39 mm, the material achieves the minimum reflection loss RL around 8.3 GHz. min = -81.806dB; Furthermore, this material achieves a maximum effective absorption bandwidth of EAB at a thickness of 2.34mm. max = 5.775 GHz.
[0060] Figure 7The graph shows the absorption performance of Co / SiC@CPAN-1200 electromagnetic wave absorbing material (fill rate 20%). It can be seen from the graph that when the material thickness is 2.05 mm, its minimum reflection loss reaches RL. min = -61.619 dB, with an absorption peak located around 15.0 GHz; meanwhile, the effective absorption bandwidth at a thickness of 2.26 mm is EAB. max = 5.775 GHz. This indicates that Co / SiC@CPAN-1200 not only has high absorption intensity, but also achieves efficient wave absorption at a thinner thickness, which is more conducive to lightweight applications.
[0061] This confirms that Co / SiC@CPAN-1100 exhibits the strongest absorption intensity among the three (Co / SiC@CPAN-1000, Co / SiC@CPAN-1100 and Co / SiC@CPAN-1200), making it one of the samples with the best overall absorption performance.
[0062] Figure 8 The graph shows the absorption performance of Fe / SiC@CPAN-1200 electromagnetic wave absorbing material (fill rate 30%). A significant absorption peak is observed in the Ku band, indicating that the material has good absorption performance in the high-frequency range. Notably, the material achieves the minimum reflection loss value RL at a thickness of 1.76 mm. min = -51.501 dB, with the absorption peak located around 16.0 GHz. This indicates that Fe / SiC@CPAN-1200 has good high-frequency absorption characteristics in thin films, especially suitable for Ku-band absorption; however, judging from the overall performance in the figure, its comprehensive absorption intensity is slightly weaker than that of the optimal Co-based sample.
[0063] Figure 9 The image shows the absorption performance of Ni / SiC@CPAN-1000 electromagnetic wave absorbing material (fill rate 20%). When the thickness is 2.55 mm, its minimum reflection loss reaches RL. min = -66.302 dB, with the absorption peak located around 8.9 GHz. This indicates that Ni / SiC@CPAN-1000 has a significant absorption advantage in the mid-frequency band, especially near the X-band. However, as shown in the figure, its effective bandwidth continuity is not as obvious as that of the Co-based sample, thus it is more inclined to be a "strong absorption peak type" material.
[0064] Figure 10 The image shows the absorption performance of Co@CPAN-1000 electromagnetic wave absorbing material (fill rate 20%). When the material thickness is 4.97 mm, its minimum reflection loss reaches RL. min= -22.663 dB, indicating that the material possesses certain microwave absorption performance at a relatively thick thickness. The absorption peaks of this material mainly appear in the C-band and Ku-band. This confirms that the impedance matching and loss synergy of the material without SiC is weaker, its optimal matching thickness is larger, and its microwave absorption performance is significantly inferior to that of the SiC composite system.
[0065] Figure 11 The image shows the absorption performance of Co@CPAN-1100 electromagnetic wave absorbing material (fill rate 20%). When the material thickness is 5.31 mm, its minimum reflection loss reaches RL. min = -41.927 dB, with the absorption peak located around 4.6 GHz, indicating strong absorption in the C-band. Overall, the absorption intensity of Co@CPAN-1100 is significantly better than that of Co@CPAN-1000. Appropriately increasing the carbonization temperature is beneficial to enhancing the microwave absorption performance of the material, but its thinning and overall microwave absorption performance are still inferior to those of the SiC composite sample.
[0066] Figure 12 The image shows the absorption performance of Co@CPAN-1200 electromagnetic wave absorbing material (fill rate 20%). When the material thickness is 4.86 mm, its minimum reflection loss reaches RL. min = -35.370 dB, with the absorption peak located around 5.1 GHz, belonging to the C-band. Its optimal absorption still depends on a relatively large thickness, indicating that although the absorption performance of the single Co@CPAN system can be improved by increasing the carbonization temperature, the improvement is limited, and overall it is still not as good as the SiC composite system.
[0067] The examples above are merely illustrative of the invention and do not constitute a limitation on the scope of protection of the invention. Any design that is the same as or similar to the invention falls within the scope of protection of the invention.
Claims
1. A fiber-based carbon-based electromagnetic wave absorbing material, characterized in that, The invention comprises a continuous carbon matrix, magnetic metal particles, and a nano-reinforcing phase. The continuous carbon matrix is formed by carbonizing a carbon precursor at high temperature. Both the carbon precursor and the magnetic metal particles are dissolved in N,N-dimethylacetamide. The magnetic metal particles are uniformly anchored and embedded in the continuous carbon matrix. The nano-reinforcing phase is uniformly dispersed within the framework of the continuous carbon matrix by physical embedding. The N,N-dimethylacetamide not only acts as a solvent, but its molecules also undergo coordination reactions with the metal ions of the magnetic metal particles; When preparing the fiber film as the electromagnetic wave absorbing material using electrospinning, coordination bonds are formed between the carbon precursor and the magnetic metal particles, anchoring the magnetic components in the fiber skeleton. At the same time, the nano-reinforcing particles, as rigid heterogeneous phases, construct a nano-reinforcing network inside the fiber.
2. The fibrous carbon-based electromagnetic wave absorbing material according to claim 1, characterized in that, The carbon precursor is polyacrylonitrile or polyvinylpyrrolidone.
3. The fibrous carbon-based electromagnetic wave absorbing material according to claim 1, characterized in that, The magnetic metal particles are cobalt acetylacetonate, iron acetylacetonate, or nickel acetylacetonate.
4. The fibrous carbon-based electromagnetic wave absorbing material according to claim 1, characterized in that, The nano-reinforcing phase is SiC.
5. A fiber-based carbon electromagnetic wave absorbing material according to any one of claims 1 to 4, characterized in that, The mass ratio of the continuous carbon matrix, magnetic metal particles, and nano-reinforcing phase is 1~1.5:0.5~0.75:0.5~0.
75.
6. A fiber-based carbon electromagnetic wave absorbing material according to any one of claims 1 to 4, characterized in that... The molecular weight (Mw) of the carbon precursor is 150,000 to 250,000 g / mol.
7. A fiber-based carbon-based electromagnetic wave absorbing material according to any one of claims 1 to 4, characterized in that, The magnetic metal particles have an average particle size of 5-70 μm, and the nano-reinforcing phase has an average particle size of 3-10 μm.
8. A method for preparing a fibrous carbon-based electromagnetic wave absorbing material as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1) The carbon precursor and magnetic metal salt are dissolved sequentially in N,N-dimethylacetamide to form a homogeneous and stable spinning solution; Step 2) Add the nano-reinforcing phase to the spinning solution and disperse it evenly to prepare a composite suspension spinning solution; Step 3) Prepare fiber films from composite suspension spinning solutions using electrospinning; Step 4) Dry the fiber film at room temperature for 10-12 hours to stabilize the fiber structure, then perform high-temperature carbonization treatment in an inert atmosphere, keep it at the temperature for 1-2 hours, and cool it naturally to room temperature to obtain the electromagnetic wave absorbing material.
9. The method for preparing a fiber-based carbon electromagnetic wave absorbing material according to claim 8, characterized in that, The parameters for electrospinning in step 3) are as follows: voltage is 25~30kv, thrust speed is 0.004~0.006mm / s, needle is 20G, and the distance between the push pump and the roller is 10~15cm.
10. The method for preparing a fiber-based carbon electromagnetic wave absorbing material according to claim 8, characterized in that, The high-temperature carbonization temperature mentioned in step 4) is 1000~1200℃.